Criminal Law Enforcement Through Customary Fines Is Linked to the Purpose of Punishment - Berli Pernado (JUSTICES: Journal of Law, 2026)
This study aims to describe and analyze the law enforcement process for these crimes through the application of customary fines and assess their suitability with the objectives of punishment in Indonesian criminal law. The study used a descriptive qualitative method with data collection techniques such as in-depth interviews, field observations, and documentation studies, as well as thematic analysis through data triangulation to ensure validity. The results show that customary fines in Seluma Regency remain a living law, accepted by the community, and considered effective. Customary sanctions are not only material but also contain social and symbolic dimensions that encourage perpetrator responsibility, reparation of victims' losses, and restoration of social harmony. This approach fulfills most of the objectives of punishment, especially restorative and rehabilitative ones, because it is able to resolve conflicts more quickly, humanely, and in accordance with local cultural values. In conclusion, the customary fine mechanism can be an alternative law enforcement that is relevant, contextual, and has the potential to support the national criminal justice system, as long as its implementation remains in line with the principles of justice, legal certainty, and respect for human rights. These findings also indicate the need for stronger synergy between state law enforcement officials and customary institutions to ensure that customary fines are enforced on a clear, coordinated basis and do not conflict with positive law. This can contribute significantly to realizing just, effective, and welfare-oriented law enforcement in Seluma Regency and other similar regions in Indonesia.